A new species of extinct fossil scops owl (Aves: Strigiformes: Strigidae: Otus) from the Archipelago of Madeira (North Atlantic Ocean) - RANDO, JUAN CARLOS; PIEPER, HARALD; ALCOVER, JOSEP ANTONI; OLSON, STORRS L. (Zootaxa, 2012)
The extinct Madeiran Scops Owl Otus mauli n. sp. is described from fossil bones found in Quaternary sites on MadeiraIsland (Madeira Archipelago, North Atlantic Ocean). It is the first extinct bird to be described from this archipelago andthe first extinct species of Strigiformes known from anywhere in Macaronesia. The forelimb bones of the new taxon aresimilar in size to those of the Eurasian Scops Owl (Otus scops Linnaeus) but the hindlimb bones are longer, especially thetarsometatarsus, which is much longer and more slender than in O. scops. The estimated body weight and wing loading,together with the proportions of hindlimb bones (femur, tibiotarsus and tarsometatarsus) in relation to total length of legbones (femur+tibiotarsus+tarsometatarsus), seem to indicate a ground-dwelling life-style. Human arrival and subsequenthabitat alterations (introduction of alien taxa, burning, etc.) are the most probable causes of its extinction. The same spe-cies or a close relative is documented from dunes on the island of Porto Santo, but the quality of preservation of its bones precludes more certain identification.